Opportunities and challenges in delivering maternal and child nutrition services through public primary health care facilities in urban Bangladesh: a qualitative inquiry - A M Rumayan Hasan; Mohammad Abdus Selim; Faugia Islam Anne; Jessica Escobar-DeMarco; Santhia Ireen; Kristen Kappos; Deborah Ash; Sabrina Rasheed (BMC, 2023)
Abstract Background Public primary health facilities are an important source of nutrition services for the urban areas in Bangladesh. We aimed to understand the challenges and facilitators of delivering maternal and child nutrition services through public sector from the perspectives of the users and service providers. Method The study was conducted in selected public primary health care facilities and their catchment area in Dhaka city from April-July 2019. We carried out 15 free listing exercises and 43 semi-structured interviews (SSI) with pregnant women and mothers of 0-24 months old children; 6 key informant interviews (KII) with facility managers and healthcare providers; and observed service delivery in 8 health facilities. Results Findings reveal that public primary health facilities address some economic and cultural barriers to access such as cost and provision of female service providers for maternal and child health services but challenges such as distance, waiting time, and cleanliness remained. In terms of service provision, there were gaps in provision of anthropometric measurement and counseling, and healthcare providers had inadequate training and therefore, knowledge of nutrition. The low priority given to nutrition services during program design hampered the delivery of nutrition services provided through urban public sector health facilities. Conclusions There were important gaps in terms of service provision and capacity of healthcare providers, and therefore, the quality of nutrition service provided through public primary health care facilities. To maximize the coverage of quality nutrition services in the urban areas, it is important to think through the design of nutrition service delivery and allocate adequate resources to fill the material and capacity gaps.